Molecular diagnosis of vitreoretinal lymphoma - Jay Jiyong Kwak; Christopher Seungkyu Lee (Taiwan Journal of Ophthalmology, 2025)
Vitreoretinal lymphoma (VRL) is a rare ocular malignancy that involves the retina, the retinal pigment epithelium, and the vitreous. It is a subtype of primary central nervous system lymphoma (CNSL). Most cases of VRL and CNSL are classified as diffuse large B-cell lymphoma. Despite its indolent nature, VRL can lead to permanent vision loss and even death due to CNS involvement. The gold standard for diagnosing VRL is the identification of lymphoma cells in a vitreous biopsy. However, diagnosis is challenging due to the rarity and fragility of lymphoma cells. Consequently, various diagnostic methods, such as interleukin level measurement, immunoglobulin clonality assays, flow cytometry, and molecular analysis have been developed to improve diagnostic accuracy. Tools from molecular biology, such as next-generation sequencing and single-cell based analyses, are being investigated as emerging diagnostic modalities. This review aims to discuss the conventional and up-to-date molecular tools for VRL diagnosis and to present important genetic variations and their clinical implications in VRL.